Produção de carvão ativado a partir da biomassa residual da castanha do Brasil (Bertholletia excelsa L.) para adsorção de cobre (II) - MELO, Selma dos Santos (Universidade Federal do Pará, 2014)
Activated carbon was produced from the Brazil nut bark (Bertholletia excelsa l.) to be used in the cooper (II) removing, in adsorption process in bath system. The bark is a waste material from the chestnut improvement which was collected, selected, washed in running water and then it was dried up in stove at 150 °C in 24 h. The carbons were charred at 400 °C for 3h and thermally activated at 800 °C in 1, 2 and 3 hours time when they received its encodings CA1, CA2 and CA3 respectively. Then they were characterized as: the specific superficial area, volume and pores size, X-ray diffraction, scanning electron microscopy (SEM) coupled to EDS (energy dispersive X-ray system) and Fourier transformed infrared spectroscopy FTIR). Preliminary tests were performed to assess the carbon efficiency as cooper (II) removing in synthetic solution of 50 mg L-1 initial concentration. As the results were satisfactory to CA1, CA2 and CA3 (93,43, 97,23 and 96,92 % to those carbons), decided by what had higher removing percentage of. The CA2 was produced and characterized as: the real and apparent densities, porosity in fixed bed, pH, moisture (wet basis), ashes, fixed carbon and functional groups by Boehm method. There were preformed tests to determine the cooper (II) efficiency removing concerning the carbon particle diameter influence, pH of the solution, contact time influence and variation of the initial concentration. The results of higher removing percentage were to diameter 0,595≤D≤1,19 mm, pH 5,09, in time of 5 min and concentrations of 50, 100 e 150 mg L-1. The adsorption kinetic study that best fit according to data was pseudo-second order model. The experimental data that presented good fit according to mathematical models of Langmuir and Frendlich isotherm. In this sense, was obtained activated carbon at a low cost from the Brazil nut bark which one showed a good efficiency in cooper (II) removing process and also allowing the using in the effluents treatment.